Drug Release Studies of Naproxen Agglomerates Produced by the Antisolvent Approach in the Presence of Hydroxypropyl Cellulose: Drug release studies of naproxen agglomerates - Maryam Maghsoodi; Sara Esmaeilzadeh (Iranian Journal of Pharmaceutical Sciences, 2011)
In this study, the effect of recrystallization of naproxen in the presence of hydroxypropyl cellulose (HPC) on the release rate of drug was investigated. Crystals were generated by the anti-solvent approach using the HPC solution in water as the anti-solvent. The samples were subjected to various physicochemical evaluations such as crystal size, scanning electron microscopy, Fourier transform infrared (FTIR) spectroscopy, solubility, wettability and dissolution studies. Results revealed that HPC play a key role in controlling the primary crystal size, morphology, size and surface properties of naproxen agglomerates. Crystallization of naproxen in the presence of HPC caused a marked modification of its dissolution. The particles obtained in the presence of HPC exhibited slower dissolution rate compared to those produced in the absence of HPC. This was attributed to the adsorption of HPC on the surface of the naproxen crystals.It was shown that the solubility of naproxen increased in solution containing HPC.Moreover, there was a significant difference between the solubility of untreated naproxen and that of samples crystallized in the presence of HPC in water. Contact angle measurements revealed that control crystals obtained in the absence of HPC have a greater contact angle than those produced in the presence of HPC. FT-IR spectroscopy results indicated the absence of any interaction between drug and HPC. This study highlights the influence of polymeric additive on the crystallization process leading to modified performance.